Análisis para la interconexión de recursos distribuidos en redes secundarias de distribución de sistemas de energía eléctrica - Armijos Espinoza, Luis Freddy (2024)
This document refers to the impact of distributed generation (DG) at home on the low voltage networks of Empresa Eléctrica Regional del Sur S.A. (EERSSA). The model consists of determining the impact that distributed generation has on the transformer and the low voltage network, improving the voltage drop and system stability. For this purpose, the data obtained from a subscriber's spreadsheet is tabulated and quantified in order to determine the monthly consumption and the improvement obtained with the entry of DG. Likewise, with the help of the electrical network analyzer equipment, the voltage levels delivered by the network are tested. Subsequently, with the support of specialized software, a flow run is performed to determine the electrical flow in the current low voltage networks, and how they act at the time of DG entry, taking into consideration the current regulations in the Ecuadorian electricity sector and the IEEE 1547 standard. Likewise, the economic benefit to the investor is determined at the moment that its mini photovoltaic power plant delivers energy to the grid and vice versa. Keywords: Subscriber, Photovoltaic Energy, Distributed Generation, Low Voltage Grid, Specialized Software.